Feed Solution in the Pipeline aith the Compensators Mortar Pump of Various Design Solutions Pressure Pulsations Degree Determination - Korobko, Bogdan; Virchenko, Viktor; Shapoval, Mykola (International Journal of Engineering and Technology, 2018)
The article deals with the mortar pump with ball spring-loaded suction and delivery valves, a special insert in the suction chamber and compensators of various design solutions. Comparative analysis to determine the degree of pressure pulsation of the mortar pump with various compensators is presented. On the basis of theoretical and experimental studies, it has been proven that mortar pump with a combined compensator of increased volume has lower pulsation levels relative to the pulsations in the mortar pump compensator with combined pressure pulsations compensator. Rational parameters of the compensator of increased mortarâ€™s volume are defined. Â Â